Automated Control and Monitoring Systems for Technological Processes in Ammonium Nitrate Production - Dovgalov, Leonid; Ushakova, Olena; Shylin, Sergii (Видавництво Львівської політехніки, 2013)
Two automated control and monitoring systems for the neutralization process in ammonium nitrate production have been elaborated. The methods are based on the dependence of measuring electrode potential on the concentration of nitric acid and ammonia in a neutralizer. The systems have been shown to be efficient in wide concentration and temperature ranges. In this paper, the monitoring system for the concentration of water in ammonium nitrate melt has been also presented. The proposed systems has been tested in industry and implemented into production.
Keywords: automated control; redox potential; neutralizer; ammonium nitrate; concentration sensor; solidification; ecofriendly production